Penggunaan Alat Kontrasepsi Keluarga Berencana pada Masyarakat Pesisir di Desa Klidang Lor Kabupaten Batang - Widyaningtyas Widyaningtyas; Utsman Utsman; Muarifuddin Muarifuddin (Ikatan Mahasiswa Pendidikan Luar Sekolah ( IMADIKLUS ), 2021)
Population growth in Indonesia is increasing. These conditions led the government to run efforts in the form of family planning programs to control the population. Specific data of KB village of Kidung Lor as research place is 86% female PUS become KB MOW acceptor. The formulation of problem in research include (1) How is the application of Contraception (Alkon) for coastal community in Klidang Lor Village of Batang Regency? (2) How are the factors that can encourage and impede the implementation of contraceptive tools (Alkon) for coastal communities in Klidang Lor village of Batang ?. This study aims to describe and analyze the application of contraceptive tools (Alkon) for coastal communities in Klidang Lor village of Batang Regency and factors that can encourage and hamper the application of contraceptive tools (Alkon) for coastal communities in Klidang Lor village, Batang regency. This research uses qualitative approach. Research location in Klidang Lor village, Batang district, and documentation. Research subjects 1 Chairman of PLKB, 1 Chairman of PPPKBD, and 3 couples of child-bearing age as informants. Data validity by using source and method triangulation. Data analysis techniques: data reduction, data display, and data verification. The results obtained in this study were: contraceptive delivery (Alkon) in the practice of family planning in Klidang Lor village, average acceptors of KB fertile couples using MOW. The supporting and inhibiting factors in this program are supported in terms of economic, health, family and good self-awareness. In addition, there are inhibiting factors consisting of EFA fear, anxiety, and lack of family planning facilities. The conclusion in this research is the application of contraception (Alkon) in the Implementation of family planning in coastal communities in Klidang Lor, Batang Regency has been running well with the success rate of KB as many as 58 people. The average age of EFAs who follow KB is 37.2 years. Similarly, in the achievement of new KB MOW participants there are 7 (86%) are MOW with independent costs. Suggestion Providing counseling or dissemination about family planning objectives is not only about regulating birth year but to decrease population growth rate to coastal communities in Klidang Lor village of Batang Regency.